Level of Knowledge and Attitude of Pregnant Women towards Contraceptive Planning with Intrauterine Contraceptive Devices - Ida Ayu Nyoman Diah Pradnyadari; I Gusti Ngurah Made Bayuningrat; Komang Trisna Sumadewi (Muhammadiyah Medical Journal, 2025)
Background: Indonesia's increasing population has prompted government efforts in family planning, with the recommended long-term contraceptive method being the intrauterine device (IUD), although its usage rate remains low. Objective: This study aimed to investigate the relationship between knowledge levels and attitudes of pregnant women toward IUD contraceptive planning. Methods: This study used an analytical, cross-sectional design. The sample consisted of 52 respondents: 26 who had used IUDs and 26 who had never used IUDs. Respondent data takers used consecutive sampling methods in accordance with the inclusion and exclusion criteria. The primary data was collected using a questionnaire. The variables used included age, education, occupation, number of children, knowledge, attitude, and IUD use. The data were analyzed using the chi-square test. Results: This study found that 57.7% of respondents were aged 21-30 years; 50.0% had a bachelor's level of education; 34.6% of respondents worked as private employees; 50.0% of respondents had one child; respondents' knowledge level was 73.1% good; and a positive attitude of 76.9%. This study also found a significant positive relationship between attitude and knowledge of IUD use, with a p<0.001 value. Conclusions: It can thus be concluded that the level of knowledge is related to the attitude of pregnant women toward the use of IUD contraception, which can be a basis for designing more effective interventions in improving public understanding and acceptance of this contraceptive method.